Coping in two cultures: an ecological study of mentally ill people and their families in rural South Africa - Cumes, Heide Ulrike (Rhodes University, Faculty of Humanities, Department of Psychology, 1995)
This study explores severe mental illness in a South African ru~al district, moving, as with a zoom lens, from the macroperspectives of (i) Xhosa culture, and (ii) biomedicine, to the lived experience of the individual. Its methodology, predominantly qualitative, employed anthropological and psychological procedures. The fieldwork (1988-1989)encompassed a three month stay in the village of Msobomvu. Patients continued to be tracked informally until June, 1995. The empirical research has three parts. In part one, the person with a mental illness was contextualized within Xhosa cosmology and social attitudes. The cognitive and social ecologies were tapped through the narratives of high school and university students at different stages of a Western-biased education. Social attitudes regarding mental illness, and confidence in treatment by traditional healers and the hospital, were also evaluated. Traditional attitudes and supernatural beliefs of illness causation persisted in spite of Eurocentric education, with a concurrent increase in the acceptance of Western-type causal explanations commensurate with continued education. Part two considered the the patients in relation to (i) the biomedical framework (the mental and local hospitals), and (ii) their readjustment to the community after hospitalization. Data came from patient charts, interviews with medical staff, and follow-up visits in the villages. Socio-political and economic issues were salient. Part three case-studied people identified by the village residents as having a mental illness. Resources for treatment - traditional healers, mobile clinic, and village health workers - were the focus. The traditional healing system, and biomedicine, were compared for effectiveness, through the course of illness events. While biomedicine was more effective in containing acute psychotic episodes than treatment by the traditional healer, lack of appropriate resources within the biomedical setting had disastrous results for patient compliance and long-term management of the illness, particularly in people with obvious symptoms of bipolar disorder. The mental hospital emerged as an agent of control. While Xhosa culture provided a more tolerant setting for people with a mental illness, the course of severe mental illness was by no means benign, despite research suggesting a more positive outcome for such conditions in the developing world.
Keywords: Mental illness -- South Africa; Xhosa (African people) -- Psychology; Xhosa (African people) -- Religion; Xhosa (African people) -- Social life and customs